2020
DOI: 10.1002/mar.21356
|View full text |Cite
|
Sign up to set email alerts
|

The effect of privacy choice in cookie notices on consumers' perceived fairness of frequent price changes

Abstract: Recent regulatory changes (i.e., General Data Protection Regulation of the European Union) enforce that seller (e.g., retail and service) and all other websites disclose through cookie notices which data they collect and store. At the same time, websites must allow consumers to disagree to the tracking of their browsing behavior. Despite sellers' concern about the loss of consumer insights-as consumers might disagree to the collection of their browsing data-cookie notices might also have a surprising sideeffec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
42
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 42 publications
(47 citation statements)
references
References 73 publications
2
42
0
3
Order By: Relevance
“…Individuals are motivated to develop and confirm their self-identity regarding social groups (Hogg et al, 1995;Islam, 2014;Tajfel & Turner, 1979). In the context of this While Schmidt et al (2020) focused on purchase behavior in response to price changes online, the current study extends our knowledge of information disclosure and its impact on priceirrelevant behavior (i.e., social media brand page engagement).…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…Individuals are motivated to develop and confirm their self-identity regarding social groups (Hogg et al, 1995;Islam, 2014;Tajfel & Turner, 1979). In the context of this While Schmidt et al (2020) focused on purchase behavior in response to price changes online, the current study extends our knowledge of information disclosure and its impact on priceirrelevant behavior (i.e., social media brand page engagement).…”
Section: Discussionmentioning
confidence: 82%
“…The antecedents of consumer-social networking site identification and information disclosure can be used in further research to better understand behavioral outcomes of consumer brand engagement, such as purchases, word-of-mouth communications, and customer loyalty.The current research broadens our understanding of the information disclosure effect on online consumer behavior. It builds on recent literature indicating that consumers' online information disclosure influences their subsequent behavior Schmidt et al (2020). demonstrated that consumers who consent to online information sharing on a website are more likely to accept price changes on the website since they attribute the price change to their own behavior.…”
mentioning
confidence: 97%
“…Therefore, financial institutions should reward companies that use this system with lower loan interest rates. Perceived fairness proved to have a significant positive effect on usage intention [62,63], which indicates that the government should play the role of a supervisor. On the one hand, the government can easily find unfair loan decisions made by financial institutions through the system.…”
Section: Discussionmentioning
confidence: 94%
“…Second, environmental dimensions such as government legislation or privacy notices (Culnan & Bies, 2003). And finally, organizational dimensions, that is, firm transparency and personalization of services through technical solutions adopted by organizations to protect users' privacy, such as opt‐in technology allowing for greater data control by consumers or the exchange of privacy for price changes (Aguirre et al, 2015; Hong et al, 2019; Martin, 2015; Schmidt et al, 2020).…”
Section: Theory and Hypothesesmentioning
confidence: 99%
“…Prior research suggests that consumer privacy subversion behavior can be overcome by organizational privacy‐enhancing factors (Aguirre et al, 2015; Foxman & Kilcoyne, 1993; Martin & Murphy, 2017; Nill & Aalberts, 2014). Building on a justice‐based perspective, research has noted that firms can increase consumers' perceived control over their information, thus increasing their willingness to share (Culnan & Bies, 2003; Etzioni, 2019; Schmidt et al, 2020). Using rational motives for moral/ethical reasoning, other studies have found that firms can increase information sharing by generating trust in the organization (Culnan & Bies, 2003; Limbu et al, 2012).…”
Section: Introductionmentioning
confidence: 99%